2023
DOI: 10.7759/cureus.47931
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship Between Unilateral/Bilateral Impacted Maxillary Canines and Nasal Septum Deviation?

Ebru Kucukkaraca

Abstract: Introduction A deviated nasal septum may be associated with some dentofacial deformities. The aim of the study was to determine whether there is a relationship between some craniomaxillary features of unilateral and bilateral maxillary impacted canines and nasal septum deviation. Methods This is a retrospective study consisting of cone beam computed tomography (CBCT) images of 51 patients. All patients were divided into three subgroups: unilateral maxillary impacted canines (UM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Studies results showed no significant differences in any of the anterior temporal, masseter muscles in the normocclusive and right posterior crossbite subjects at rest position [2]. Kecik et al (2007) showed that the anterior temporal and masseter muscle activity at rest position differed signifi-cantly between the crossbite and control groups, and higher muscle activity was found on the crossbite side [13]. Children with a narrowing upper jaw and a unilateral posterior crossbite had a different pattern of EMG activity from children of the control group.…”
Section: Discussionmentioning
confidence: 85%
“…Studies results showed no significant differences in any of the anterior temporal, masseter muscles in the normocclusive and right posterior crossbite subjects at rest position [2]. Kecik et al (2007) showed that the anterior temporal and masseter muscle activity at rest position differed signifi-cantly between the crossbite and control groups, and higher muscle activity was found on the crossbite side [13]. Children with a narrowing upper jaw and a unilateral posterior crossbite had a different pattern of EMG activity from children of the control group.…”
Section: Discussionmentioning
confidence: 85%